The AB Procedure and Capital Budgeting - Beranek, William (Journal of Financial and Quantitative Analysis, 1980)
In a recent paper the net present value (NPV) accept-reject decision rule, invoking the conventional definition of expected net cash flows of a finite, uneven character along with a weighted average cost of capital, was derived from the condition of shareholder wealth maximization (Beranek [2]). Since the entire textbook-NPV expression was established–its logical form, the content of its variables, and the implied specification of its parameters–this has served as a partial rescue of textbook approaches to capital budgeting, approaches which had heretofore rested on an intuitive basis. But attempts to rescue textbook treatments of mutually exclusive (ME) choices and capital rationing must fail. Explaining why they must fail, and developing what we shall denote as the AB alternative solution, is the object of this paper.